Processed food intake assortativity in the personal networks of older adults - Marian-Gabriel Hâncean; Jürgen Lerner; Matjaž Perc; José Luis Molina; Marius Geantă; Iulian Oană; Bianca-Elena Mihăilă (Scientific Reports)
Abstract Existing research indicates that dietary habits spread through social networks, yet the impact on populations in Eastern Europe, particularly in rural areas, is less understood. We examine the influence of personal networks on the consumption of high-salt processed foods among individuals in rural Romania, with a specific focus on older adults. Using a personal network analysis, we analyze data from 83 participants of varying ages and their social contacts through multi-level regression models. The inclusion of participants across a wider age range allows us to capture the broader dynamics of social networks, reflecting the intergenerational nature of rural communities. Our findings reveal assortativity in dietary habits, indicating that individuals cluster with others who share similar food consumption patterns. Our results underscore the need for public health interventions that account for the influence of social networks on dietary behavior, as addressing high salt intake and its associated health risks may require considering the broader social context beyond older adults. The study contributes to understanding the social determinants of dietary behaviors and highlights the role of personal networks in shaping food choices in vulnerable populations.